Blockade of NOX2 and STIM1 signaling limits lipopolysaccharide-induced vascular inflammation - Gandhirajan, Rajesh Kumar (American Society for Clinical Investigation, 2013)
During sepsis, acute lung injury (ALI) results from activation of innate immune cells and endothelial cells by endotoxins, leading to systemic inflammation through proinflammatory cytokine overproduction, oxidative stress, and intracellular Ca(2+) overload. Despite considerable investigation, the underlying molecular mechanism(s) leading to LPS-induced ALI remain elusive. To determine whether stromal interaction molecule 1–dependent (STIM1-dependent) signaling drives endothelial dysfunction in response to LPS, we investigated oxidative and STIM1 signaling of EC-specific Stim1-knockout mice. Here we report that LPS-mediated Ca(2+) oscillations are ablated in ECs deficient in Nox2, Stim1, and type II inositol triphosphate receptor (Itpr2). LPS-induced nuclear factor of activated T cells (NFAT) nuclear accumulation was abrogated by either antioxidant supplementation or Ca(2+) chelation. Moreover, ECs lacking either Nox2 or Stim1 failed to trigger store-operated Ca(2+) entry (SOCe) and NFAT nuclear accumulation. LPS-induced vascular permeability changes were reduced in EC-specific Stim1(–/–) mice, despite elevation of systemic cytokine levels. Additionally, inhibition of STIM1 signaling prevented receptor-interacting protein 3–dependent (RIP3-dependent) EC death. Remarkably, BTP2, a small-molecule calcium release–activated calcium (CRAC) channel blocker administered after insult, halted LPS-induced vascular leakage and pulmonary edema. These results indicate that ROS-driven Ca(2+) signaling promotes vascular barrier dysfunction and that the SOCe machinery may provide crucial therapeutic targets to limit sepsis-induced ALI.